(untitled) (World Bulletin of Social Sciences, 2022)
The article presents the concept of the political process, its peculiarities, the views of world scholars on political processes from a political point of view, the classical approaches. The current state of political processes is comparatively analyzed on the basis of materials from independent Uzbekistan and neighboring countries.